Comparison Study between Surface Bending and Base Bending in the Bending Strength and the Microstructure Variation for FSWed ZM6 Sheet. Issue 2 (21st October 2022) - Chen, Wenzhen; Yuan, Manman; Wang, Wenke; Yu, Jun; Zhang, Wencong; Teng, Tianyue
Abstract : Herein, the surface bending and base bending effect on the bending strength and the microstructure variation of ZM6 magnesium alloy sheet that is fabricated by friction stir welding are compared. The microstructure results show that the base bending produces about 22.1% of tensile twins in the center of stirring zone (SZ‐C), while only about 3.7% of tensile twins in the advancing side of stirring zone (SZ‐AS). However, the surface bending results in the opposite result, that is, about 21.8% of tensile twins are generated in the SZ‐AS, while only 7.2% of tensile twins are generated in the SZ‐C. These microstructure variations are characterized by the macroscopical Schmid factor, which is calculated according to the microscopic Schmid factor of each deformation mechanism and their respective area fractions. Such macroscopical Schmid factor is closely related to the yield strength. Abundant prismatic slip (about 45%) is activated in surface bending, producing the higher macroscopical Schmid factor and the yield strength. By contrast, the activation fraction of the prismatic slip is only 13%, and this gives rise to the lower macroscopical Schmid factor, eventually decreasing the yield strength. Abstract : The microstructure and mechanical properties between surface bending and base bending of ZM6 magnesium alloy plate fabricated by friction are compared. The equivalent Schmid factor calculated based on the local stress state could be well explained the difference of yield strength between surface bending and base bending of friction stir welded plates.